ANALISIS SARANA ANGKUTAN UMUM DAMRI RUTE DAYA MURNI – UNIT 2 KABUPATEN TULANG BAWANG BARAT - Hedi Saputra; Sugito Sugito; Sep Aan Ansori; Waris Waris; Teguh Santoso (PT. Saha Kreasi Indonesia, 2026)
West Tulang Bawang Regency is a region experiencing rapid development across various sectors, which has led to increased population mobility and a growing demand for adequate transportation systems. One of the public transportation services operating in this area is the DAMRI public transport on the Daya Murni – Unit 2 route. However, limitations in the number of vehicles and operating hours indicate the need for an evaluation of the quality of service provided. This study aims to analyze users’ perceptions of the DAMRI public transportation service based on the indicators of Safety (security and safety), Comfort, Accessibility, Reliability, Cost affordability, Efficiency of service, and overall user satisfaction, as well as to evaluate service quality across all aspects. The research method employed is quantitative descriptive analysis using a survey approach, with data collected through the distribution of questionnaires to 100 respondents, determined using the Slovin formula. Secondary data were obtained from Perum DAMRI and related institutions. The research instrument utilized a five-point Likert scale, and the results of the analysis were classified using class interval methods. The results of the study indicate that users’ perceptions of the seven indicators show average scores ranging from 3,98 to 4,03 which fall into the “good” category. Furthermore, the overall quality of public transportation services based on all aspects achieved a total average score of 87,93 also classified as “good”. These findings demonstrate that the service quality of the DAMRI public transportation on the Daya Murni – Unit 2 route, based on users’ perceptions, is in the good category.